Patterns of cancer occurrence in a tertiary care centre - Bhagyalakshmi, Atla; Venkatalakshmi, Anem; Subhash, Regidi; kumar, Seeram Satish (International Journal of Research in Medical Sciences, 2017)
Background:This study is an attempt to know the incidence of cancer in a tertiary care centre. Statistics for all newly diagnosed cancer cases by correlation with factors like age, gender & organ systems involved with complete histopathological evaluation is presented. Emphasis is given to segregating each cancer and grouping them into their respective order for statistical analysis. Objectives of the study was to conduct a prospective statistical analysis, computing and comparing rates, ratios and percentages of cancer incidence in relation to epidemiological parameters like age, gender, organ system and site involved, etc. and correlating with other national and international studies. Methods: All newly diagnosed cancer cases from various surgical and medical specialities were consolidated into a core database and various statistical outputs were worked out, like cancer incidence comparative rate, ratios and percentages for parameters like age distribution to gender wise, system wise, organ wise, etc. Results: Out of total 2278 cancer cases, in males (1003 cases/44.03%), tumors of head and neck (468 cases/20.54 %) were most common, and among which oral cavity cancers (278 cases/59.4 %) were most common. In females (1273 cases/55.9 %), cervical cancers (314 cases/13.7 %) were most common followed by breast cancers (218 cases/9.56 %). In children (69 cases/3.03 %) hematopoietic neoplasms (17 cases/30.3 %) were most common. Conclusions: The current study mainly summarizes the different patterns of cancer incidence in the tertiary care centre region. Cancer incidence is increasing gradually among the population and there is raise of cancer incidence in females compared to their counterparts.